2021
DOI: 10.1016/j.sleepx.2021.100040
|View full text |Cite
|
Sign up to set email alerts
|

No improvement of sleep from vitamin D supplementation: insights from a randomized controlled trial

Abstract: Background Vitamin D has been linked to sleep health in observational studies. Data from randomized controlled trials (RCTs) with vitamin D is scarce. Methods This study presents the results of a secondary analysis of 189 vitamin D insufficient participants (47.1% women) in a previously performed RCT, of which 92 were randomized to vitamin D (100,000 IU (2500 μg) as a bolus dose followed by 20,000 IU (500 μg) per week), and 97 to placebo. At baseline and after 4 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…However, this matter is still debatable as vitamin D supplementation might not show notable improvement in sleep quality, as observed in similar studies. 32 Considering these contradictory results, we suggest a better interventional study involving multiple centres, as the present study showed some technical setbacks. As a cross-sectional study with a small sample size, not only could it establish a causal relationship between observed variables, it didn't rule out a possible bidirectional relationship either.…”
Section: Discussionmentioning
confidence: 67%
“…However, this matter is still debatable as vitamin D supplementation might not show notable improvement in sleep quality, as observed in similar studies. 32 Considering these contradictory results, we suggest a better interventional study involving multiple centres, as the present study showed some technical setbacks. As a cross-sectional study with a small sample size, not only could it establish a causal relationship between observed variables, it didn't rule out a possible bidirectional relationship either.…”
Section: Discussionmentioning
confidence: 67%
“…6 nmol/L (31.2 ± 16.2 ng/mL) after 12 weeks) [87]. Regarding sleep quality, there is no evidence from RCTs for any beneficial effect of vitamin D supplementation, without any difference according to baseline vitamin D status [88,89].…”
Section: Menopausal Symptomatologymentioning
confidence: 99%
“…Por fim, evidências sugerem a participação da vitamina D na expressão de genes do relógio circadiano central 4,25 .…”
Section: Métodounclassified